Caseous lymphadenitis in a goat - Abdullah, Faez Firdaus Jesse; Osman, Abdinasir Yusuf; Adamu, Lawan; Azri, Nurul Alia; Haron, Abdul Wahid; Saad, Mohd Zamri; Omar, Abdul Rahman; Saharee, Abdul Aziz (Nexus Academic Publishers, 2013)
Despite the sero–positivity of caseous lymphadenitis (CLA) in Malaysian farms, cases with clinical signs of CLA are rarely encountered. An 8–month–old Saanen breed of goat was reported with a history of a subcutaneous mass beneath the jaw, on the right side. The consistency of the mass was non–movable, solid and hard on deep palpation. A tentative diagnosis of caseous lymphadenitis (CLA) was made based on the characteristic of the lesions presented and its contagious nature. The mass was incised and the purulent aspirate showed growth of Corynebacterium pseudotuberculosis on culture. Agar gel precipitation test (AGPT) was positive for Corynebacterium pseudotuberculosis. The mass was lanced and routine wound flushing resulted in recovery.